Choice of Library and Information Science in a rapidly changing information landscape: A systematic literature review. Issue 8 (9th November 2015) - Moniarou-Papaconstantinou, Valentini; Vassilakaki, Evgenia; Tsatsaroni, Anna
Abstract : Purpose: – Library and Information Science (LIS) has for a long time tried to gain legitimacy. In an ever changing environment due to technological and economic developments, the motivations behind choice of LIS are still of great interest. The purpose of this paper is to provide a systematic review of studies investigating the motivations that determine the choice of LIS. Design/methodology/approach: – Different search terms were run on different but relevant databases. A number of inclusion and exclusion criteria were applied and in total 45 papers were judged as relevant to choice of LIS discipline. A thorough analysis of these papers' content revealed three main themes: choice of LIS, choice of LIS specialty and career change to LIS. Findings: – A variety of different motivations for choosing LIS were identified. The same motivations were reported in all groups (high school students, students, professionals). Specifically, love of books and reading, nature of library work, desire to help people were among the most reported motivations. LIS was also chosen as a second career by different professionals mainly due to changes in their first career work environment, the nature of library work, the desire to use knowledge and the transferable skills in their new career. Research limitations/implications: – This study considered only peer-reviewed research published between 2000 and 2014 in English. Specifically, it focussed on the motivations that specific groups chose to study LIS both as first and second career. Practical implications: – Library schools could raise awareness among high school students regarding the value, role and importance of LIS. Originality/value: – This paper examines the factors influencing the choice of LIS in a changing information environment, and sheds light on the individuals' decision-making process attracted to LIS.